2017
DOI: 10.1142/s0129183117500176
|View full text |Cite
|
Sign up to set email alerts
|

Social network analysis of character interaction in the Stargate and Star Trek television series

Abstract: This paper undertakes a social network analysis of two science fiction television series, Stargate and Star Trek. Television series convey stories in the form of character interaction, which can be represented as “character networks”. We connect each pair of characters that exchanged spoken dialogue in any given scene demarcated in the television series transcripts. These networks are then used to characterize the overall structure and topology of each series. We find that the character networks of both series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Verbal dialogue can be used to construct the network (Jones, 2020;Jones et al, 2020). Character network analysis has been used in both film (Jones, 2020;Jones et al, 2020;Park et al, 2012;Weng et al, 2009) and television series (Bost et al, 2018;Tan et al, 2017) and provides the methods to successfully investigate the use of language in television as recommended by Bednarek (2018).…”
Section: Character Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Verbal dialogue can be used to construct the network (Jones, 2020;Jones et al, 2020). Character network analysis has been used in both film (Jones, 2020;Jones et al, 2020;Park et al, 2012;Weng et al, 2009) and television series (Bost et al, 2018;Tan et al, 2017) and provides the methods to successfully investigate the use of language in television as recommended by Bednarek (2018).…”
Section: Character Network Analysismentioning
confidence: 99%
“…Verbal dialogue can be used to construct the network (Jones, 2020; Jones et al, 2020). Character network analysis has been used in both film (Jones, 2020; Jones et al, 2020; Park et al, 2012; Weng et al, 2009) and television series (Bost et al, 2018; Tan et al, 2017) and provides the methods to successfully investigate the use of language in television as recommended by Bednarek (2018). Social network methods are underused in nursing research (Parnell & Robinson, 2018) and the application in the present study is unique compared with other nursing studies which predominantly seek to describe the network structure (see Benton et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, filmmaking has been studied in terms of actor networks-where two actors are connected if they appeared together in a movie. One of the more recent attempts in this direction is the social network analysis of character interactions in the Stargate and Star Trek television series [80]. Research revealed that the character networks of both series have small-world properties, and that the underlying network structure of an episode can tell us something about the complexity of the storyline in that particular episode.…”
Section: Visual Artsmentioning
confidence: 99%
“…It has been found that fictional social networks are small-world, highly clustered, and hierarchical, as real social networks [38,39], but typically differ from real ones in connectivity and levels of assortativity [40]. Most importantly, these empirically network-based analyses of character interactions have been proven to successfully find communities, identifying influential characters, and evaluating the complexity of a storyline [41][42][43].…”
Section: Introductionmentioning
confidence: 99%